The Development of AC33932 Thai Language Community Club Curriculum to Develop Learning and Innovation Skills Using Problem-based Learning for Grade 10-12 Students - Mungchopklang, Kittiya; Art-In, Dr.Sitthipon (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
This study aimed at develop the curriculum and improve learning and innovation skills using Problem-Based Learning. The results of the study were as follows: 1) The result of the development of the curriculum is highly corresponding (= 4.39, S.D. = 0.28) 2) The result for developing learning and innovation skills were the followings: 2.1) The students had average score of critical thinking and problem solving at 81.25% and students meeting the criteria-90.00% of all participants which was higher than the determined norm. 2.2) The students had average score of communication and collaboration at 82.50 and students meeting the criteria-100% of all students which was higher than the determined standard. 2.3) The students had average score of creative and innovation at 81.50% and students meeting the criteria-73.33% of all participants which was higher than the determined figure.